Probamon: jogo para o ensino de conceitos básicos de probabilidade e estatística - Seraphim, Gabriel Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
This work proposes the conception of an educational game, with the objective of promoting the incentive of studying probability and statistics subject. Therefore, researches were raised related to the legibility of the electronic games application in the teaching-learning process. In addition, the current scenario of games related to the theme was verified, noticing a strong lack in the national panorama. After planning the game mechanics, structural development has began on Unity game engine and the visual development on Blender engine. The game fits into the turn-based Role-Playing Game genre and has portability to mobile devices and computers. With the game finished, the validation and testing stage has began with the high school and technician ETEC Rosa Perrone Scavone students, located in Itatiba - SP. It was found that 62 students answered the questionnaire about the game, reporting a positive experience. It is hoped that the game can contribute to stimulating knowledge, encouraging teachers and students to adopt a more active learning methodology.

O trabalho tem como proposta a criação de um jogo educativo, com o objetivo de incentivar ao estudo de probabilidade e estatística. Para tanto, foram levantadas pesquisas relacionadas a legibilidade da aplicação de jogos eletrônicos no processo ensino-aprendizagem. Além disso, verificou-se o atual cenário de jogos relacionados ao tema, notando-se uma forte carência no panorama nacional. Após o planejamento das mecânicas do jogo, iniciou-se o desenvolvimento estrutural na Unity game engine e visual Blender engine. O jogo se enquadra no gênero Role-Playing Game de turno e possui portabilidade para dispositivos móveis e computadores. Ao finalizar o jogo, iniciou-se a etapa de validação e testes junto a 62 alunos da escola de ensino médio e técnico ETEC Rosa Perrone Scavone, do município de Itatiba - SP. Verificou-se o relato de aprovação de sua experiência com o jogo. Espera-se que o jogo possa contribuir para o ensino de probabilidade e estatística, encorajando os professores e alunos a uma metodologia de aprendizagem mais ativa.
Probamon: game for teaching basic concepts of probability and statistics
Keywords: Game development; Educational game; Probability and statistics; Jogos educativos; Jogos eletrônicos; Jogos de probabilidades (Matemática)